1992
DOI: 10.1161/01.str.23.2.267
|View full text |Cite
|
Sign up to set email alerts
|

Neurological and behavioral outcomes of focal cerebral ischemia in rats.

Abstract: Background and Purpose: The aim of this study was to investigate the neurobehavioral consequences of focal ischemia in rats.Methods: We induced permanent occlusion of the left middle cerebral artery in 14 SpragueDawley rats, and used 13 sham-operated rats as controls. During surgery, brain temperature and body temperature were kept at normothermia. Neurobehavioral studies (neurological examination, passive avoidance task, Y maze test, and modified open-field test) were carried out 4 days after ischemia before … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
102
1

Year Published

1995
1995
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(109 citation statements)
references
References 27 publications
6
102
1
Order By: Relevance
“…Using the open fi eld test according to the criteria established at our institution 16 , we observed reduction of exploratory activity (rearing and sniffing) and of defecation on the 1st postoperative day in all animals of the ischemic groups. Despite differences in the elaboration and execution of the tests, our results agree with those reported by Wahl et al 6 regarding the absence of a correlation between the behavioral and histopathological changes.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Using the open fi eld test according to the criteria established at our institution 16 , we observed reduction of exploratory activity (rearing and sniffing) and of defecation on the 1st postoperative day in all animals of the ischemic groups. Despite differences in the elaboration and execution of the tests, our results agree with those reported by Wahl et al 6 regarding the absence of a correlation between the behavioral and histopathological changes.…”
Section: Discussionsupporting
confidence: 92%
“…Another study did not detect correspondence between the behavioral and histopathological effects provoked by coagulation of the MCA in rats 6 . Using the open fi eld test according to the criteria established at our institution 16 , we observed reduction of exploratory activity (rearing and sniffing) and of defecation on the 1st postoperative day in all animals of the ischemic groups.…”
Section: Discussionmentioning
confidence: 91%
“…In these studies, 50 or 60 mg/kg G-CSF was administered via a single subcutaneous injection, and their findings formed the basis for the present study. However, changes in lesion volume do not always represent changes in functional outcome and, while some studies show that lesion size correlates with functional deficit (Rogers et al, 1997), others show it does not (Hattori et al, 2000;Reglodi et al, 2003;Wahl et al, 1992). In the current study, we measured lesion volume at 48 hours, and so it is not possible to rule out the possibility that G-CSF simply delayed the development of the lesion rather than reduced it.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that damage to the cerebral cortex or to the striatum might thus also involve a deficit of learning and memory after MCA occlusion in the passive-avoidance task (Yamamoto et a!., 1988), the Y -maze task (Wahl et a!., 1992), or the water-maze task (Markgraf et a!., 1992). In the ra dial-maze task, the rats with single lesions of the caudate nucleus or neocortex showed cognitive def icits, but this deficit later gradually recovered (Cook and Kesner, 1988;Colombo et a!., 1989;Kesner et al, 1989;Packard et a!., 1989).…”
Section: Discussionmentioning
confidence: 99%